Waist hip ratio: an anatomical predictive marker of risk of PCOS - Yadav, Sumitra; Tarware, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Polycystic ovarian syndrome (PCOS) is one of the most common endocrine disorders seen in infertility clinic of Gynae OPD. It is basically is disease of metabolic disorder and requires ultrasound and hormonal assay for its diagnosis. Methods: The study was carried out in the GOPD of MGM medical College and M.Y. Hospital Indore (M.P.) India. It included 200 women in the age group 18-40 years diagnosed as PCOS and who were compared with 200 women of same age group without PCOS. The height, weight BMI and waist hip ratio were measured and analyzed statistically. Results: The present study shows that women with PCOS had higher incidence of acne hirsutism and irregular menses (p<0.0001), women with PCOS had higher mean ovarian volume measurement (11±1.4cc) compared to female controls who had lower volume of ovary with a range of (7.94±2.34cc. (p<0.0001) as calculated by USG by sonologist. Conclusions: The presence of central obesity, (waist hip ratio >0.87) is an indication for presence of PCOS. Thus, these patients may undergo further hormone evaluation and this simple measurement can help to screen out PCOS from general population. This prevents financial burden on low resource settings.